Causal Relationship Model affecting Tourist Loyalty of a Secondary City on the East Coast - Tongkaw, Anurak; Saethow, Phannaphat; Sahunan, Sayanon (Dusit Thani College Journal, 2020)
The purpose of this research was to study the causal relationship affecting tourist loyalty of a Secondary City on the East Coast. The data was collected from 1,050 tourists of a Secondary City on the East Coast by Multi-Stage Sampling. The tool used for data collection was a 5-level rating scale questionnaire with content validity value (S-CVI/Ave) 0.88 and a reliability coefficient of 0.98. The causal relationship model was performed with the Amos program. The results showed that Service Quality, Tourism Image, and Satisfaction were affected by the loyalty of tourists with the most affected being Satisfaction. From the above results, the strategy of development of a Secondary City on the East Coast showed that there is a necessity for public relations regarding a place that tourists will always want to visit, ensuring that beautiful sights and attractions are always properly maintained. The causal relationship affecting tourist loyalty of a secondary city on the East Coast was congruent with the empirical data according to the statistical values of Chi square = 50.10, df=36, p-value=0.06, relative Chi-square (c2/df)=1.39, GFI=0.99, AGFI=0.98, CFI=0.99, NFI=0.99, TLI=0.99 RMR=0.00, RMSEA=0.019. The contribution of this research was the development of sustainable tourism guidelines.